2006
DOI: 10.1074/jbc.m601640200
|View full text |Cite
|
Sign up to set email alerts
|

A Common Site of the Fc Receptor γ Subunit Interacts with the Unrelated Immunoreceptors FcαRI and FcϵRI

Abstract: The transmembrane (TM) region of the Fc receptor-␥ (FcR␥) chain is responsible for the association of this ubiquitous signal transduction subunit with many immunoreceptor ligand binding chains, making FcR␥ key to a number of leukocyte activities in immunity and disease. Some receptors contain a TM arginine residue that interacts with Asp-11 of the FcR␥ subunit, but otherwise the molecular basis for the FcR␥ subunit interactions is largely unknown. This study reports residues in the TM region of the FcR␥ subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…This same arginine is also absent in the transmembrane region of βc. In addition, we showed here that leucine-21 in the transmembrane region of FcRγ, a residue required for both arginine-dependent and independent associations 33 , is dispensable for physical and functional association of βc with FcRγ, suggesting that this association occurs via a mode distinct from those previously known for FcRγ.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This same arginine is also absent in the transmembrane region of βc. In addition, we showed here that leucine-21 in the transmembrane region of FcRγ, a residue required for both arginine-dependent and independent associations 33 , is dispensable for physical and functional association of βc with FcRγ, suggesting that this association occurs via a mode distinct from those previously known for FcRγ.…”
Section: Discussionmentioning
confidence: 82%
“…In a group of FcRγ-associated receptors including FcαRI (also termed CD89), NKp46, the platelet collagen receptor glycoprotein VI and the paired Ig-like receptor A, an arginine residue in their transmembrane regions is required for interaction with the negatively charged aspartic acid residue in FcRγ 40 . In contrast, receptors such as FcεRI, FcγRI and FcγRIII lack the canonical transmembrane arginine but are nevertheless able to associate with FcRγ through mechanisms still not fully understood 33 . This same arginine is also absent in the transmembrane region of βc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6A, LMIR7 differed from LMIR4 by only three amino acid residues in the transmembrane domain. As it is generally accepted that a transmembrane structure plays a critical role in receptor interaction (15,24,25), we generated a chimera receptor composed of an extracellular domain, LMIR7, a transmembrane domain, LMIR4, and an intracellular domain, LMIR7, designated LMIR7-M1. When Ba/F3 cells were transduced with Myctagged LMIR-M1 as well as Myc-tagged LMIR4, LMIR7, or mock, flow cytometric analysis using anti-Myc mAb showed that surface expression levels of LMIR7-M1 were equivalent to those of LMIR4 and lower than those of LMIR7 (Fig.…”
Section: Strong Interaction Of Lmir4 With Fcr␥ In Comparison With Lmimentioning
confidence: 99%
“…In addition, FcR␥ interacts with various activating receptors such as paired Ig-like receptor A (PIR-A) (22) or platelet collagen receptor glycoprotein VI (23). Although the Arg/Asp charge interaction between transmembrane domains is well characterized, recent studies have also implicated a transmembrane leucine zipper-like interaction between activating receptors and FcR␥ (24,25). However, the relevant molecular mechanism remains incompletely understood.…”
mentioning
confidence: 99%